Platão e a adequação das palavras: uma leitura do Crátilo - Cruz, Marcílio Bezerra (2023)
This research offers a reading of Cratylus that unifies the main discursive elements of the work around a possible conception of Plato about the adequacy of words (περὶ ὀνομάτων ὀρθότητος). It discusses overcoming the impasses that conventionalist and naturalist theses lead to, especially with regard to the impossibility of saying falsehoods (ψευδῆ λέγειν) and the ability of words to raise what they intend to name. For this, we argue that Plato correlates elements present in both theses, in which the arrangement of sounds and syllables is given in a conventional way, but the meaning of words points to what is most substantial in things. Thus, words are μίμησις of οὐσίαι: they must teach (διδάσκω) and distinguish (διακρίνω) the fundamental elements of reality, helping us to apprehend and communicate knowledge. It recognizes, according to the Critical Model of interpretation of passage 439b, that such knowledge will always be flawed and imprecise, given the very limitations of words and our inability to directly contemplate and apprehend the οὐσίαι. As for the methodological procedures, it is a research of a theoretical nature, carried out from the bibliographic survey among the main authors and theses related to the study of the Cratylus, in order to explore and promote a possible reading of the dialogue. In view of this proposal, it is concluded that philosophical activity is indispensable for the improvement of human communication, since Plato attributes to διαλεκτικός the fundamental role of examining the use of words in terms of the ideas they want to communicate. We hope that the research can offer a greater understanding of the role of words within Platonic philosophy, highlighting their qualities and limitations in the processes of apprehension and communication of knowledge.